Phenylketonuria: central nervous system and microbiome interaction - Demian Arturo Herrera Morban (Hygeia Press di Corridori Marinella, 2017)
Phenylketonuria (PKU) is an autosomal recessive inborn error of metabolism characterized by increased phenylalanine (Phe) levels causing an inadequate neurodevelopment; the treatment of PKU is a Phe-restricting diet, and as such it can modulate the intestinal microbiome of the individual, generating central nervous system secondary disturbances that, added to the baseline disturbance, can influence the outcome of the disease.